Microinjection of melanin-concentrating hormone (MCH) into the median raphe nucleus promotes REM sleep in rats - Pascovich, Claudia; Niño, Sofia; Mondino, Alejandra; Lopez-Hill, Ximena; Urbanavicius, Jessika; Monti, Jaime; Lagos, Patricia; Torterolo, Pablo (Sleep Science, 2021)
Melanin concentrating hormone (MCH) is a sleep-promoting neuromodulator synthesized by neurons located in the postero-lateral hypothalamus and incerto-hypothalamic area. MCHergic neurons have widespread projections including the serotonergic dorsal (DR) and median (MnR) raphe nuclei, both involved in the control of wakefulness and sleep. In the present study, we explored in rats the presence of the MCH receptor type 1 (MCHR-1) in serotonergic neurons of the MnR by double immunofluorescence. Additionally, we analyzed the effect on sleep of MCH microinjections into the MnR. We found that MCHR-1 protein was present in MnR serotonergic and non-serotonergic neurons. In this respect, the receptor was localized in the primary cilia of these neurons. Compared with saline, microinjections of MCH into the MnR induced a dose-related increase in REM sleep time, which was related to a rise in the number of REM sleep episodes, associated with a reduction in the time spent in W. No significant changes were observed in non-REM (NREM) sleep time. Our data strongly suggest that MCH projections towards the MnR, acting through the MCHR-1 located in the primary cilia, promote REM sleep.
Keywords: Serotonin; Hypothalamus; Sleep, REM; Peptide; Paradoxical Sleep; Slow Wave Sleep